2014
DOI: 10.5944/openpraxis.6.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Opening Teaching Landscapes: The Importance of Quality Assurance in the Delivery of Open Educational Resources

Abstract: Scholars are increasingly being asked to share teaching materials, publish in open access journals, network in social media, and reuse open educational resources (OER). The theoretical benefits of Open Educational Practices (OEP) have become understood in the academic community but thus far, the use of OER has not been rapidly adopted. We aim to understand the challenges academics face with in attempting to adopt OEP, and identify whether these are related to or stem from the functionalities afforded by curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 22 publications
(21 reference statements)
4
31
0
3
Order By: Relevance
“…Those teachers who were using OER encountered similar obstacles. This finding is in agreement with Atenas, Havemann, and Priego (2014), who showed that time consumption, search ability, lack of training, licensing issues, and technical skills were the main barriers. Interestingly, lack of OER policies as a barrier to using OER was ranked only seventh and thus much lower than previous research has reported (Andrade et al, 2011).…”
Section: Teachers Willing To Collaborate With the Researchersupporting
confidence: 92%
“…Those teachers who were using OER encountered similar obstacles. This finding is in agreement with Atenas, Havemann, and Priego (2014), who showed that time consumption, search ability, lack of training, licensing issues, and technical skills were the main barriers. Interestingly, lack of OER policies as a barrier to using OER was ranked only seventh and thus much lower than previous research has reported (Andrade et al, 2011).…”
Section: Teachers Willing To Collaborate With the Researchersupporting
confidence: 92%
“…Research studies deal with this broad definition of OEP in various ways. Some focus primarily on the OER aspects of OEP (Armellini & Nie, 2013;Atenas, Havemann, & Priego, 2014;Hogan, Carlson, & Kirk, 2015;Karunanayaka, Naidu, Rajendra, & Ratnayake, 2015;Murphy, 2013;Schreurs et al, 2014). Other studies explore broader aspects of OEP such as open pedagogies and learning in open networks (Casey & Evans, 2011;Nascimbeni & Burgos, 2016; …”
Section: Open Educational Practices (Oep)mentioning
confidence: 99%
“…Για τη διασφάλιση της ποιότητας των αποθετηρίων ΑΕΠ, πρέπει να εξασφαλίζονται οι προϋποθέσεις με τις οποίες πρέπει να αξιολογούνται και να επικαιροποιούνται διαρκώς. Τα συμπεράσματα που εξάγονται σχετίζονται άμεσα με την προώθηση καινοτόμων παιδαγωγικών μοντέλων όπως προτείνουν οι Atenas, Havemann & Priego, (2014) καθώς και με τον σωστό σχεδιασμό των αποθετηρίων που εμπεριέχουν ανοικτές εκπαιδευτικές πρακτικές. Οι δείκτες διασφάλισης της ποιότητας που ελέγχουν την παραγωγή, τη χρήση και επαναχρησιμοποίηση υψηλής ποιότητας Ανοικτών Εκπαιδευτικών Πόρων μέσω θεσμοθετημένων πολιτικών, μπορούν να παράγουν και να υποστηρίξουν καινοτόμα παιδαγωγικά μοντέλα.…”
Section: σύνοψηunclassified